Big Five Factors and Employees’ Voice Behavior among Employees in Small-Medium Enterprise in Penang - Loo, Siew Pine; Desa, Nasina Mat; Asaari, Muhammad Hasmi Abu Hassan (Universiti Sains Malaysia, 2016)
This paper examined the relationship between the Big Five factors (openness to experience, conscientiousness, extraversion, agreeableness and neuroticism) and employees’ voice behavior among employees of SME in Penang. The independent variables are the Big Five factors while the dependent variable is employees’ voice behavior. The hypothesized relationship between the Big Five factors and employees’ voice behavior is based on a logical argument that those who demonstrate Big Five factors would be positively and negatively related to employees’ voice behavior to their superior. The theories that support the theoretical framework are the theory of individual difference in task and contextual performance. A total of 292 questionnaires were distributed to employees of a small-medium enterprise in Penang. A total of 108 usable questionnaires were returned yielding a usable response rate of 74%. The collected data were analyzed statistically using multivariate statistics. Factor analysis, reliability analysis, descriptive analysis, correlational analysis, and regression analysis were used as the bases of analyses. The results only indicated that agreeableness and neuroticism among the five independent variables were significantly related to employees’ voice behavior, but positively significant, which did not support the hypotheses of the study. Therefore, all the hypotheses were not supported by the study results.